Exploring the Potential of Solar Energy in Mosque Buildings: A Case Study of Dumai Islamic Centre Mosque in Riau Province, Indonesia - Nia Armelia Putri; Ari Rahman; I Wayan Koko Suryawan (Universitas Diponegoro, 2023)
This study investigated the implementation of solar panels in the Dumai Islamic Centre (DIC) Mosque, located in Dumai City, Riau Province, to reduce carbon emissions. The study presents an overview of the significance of solar energy utilization and its potential benefits in the context of mosque buildings. This research was aimed to assess the criteria for selecting the appropriate solar panel type, determine the power output and PV area required for the DIC Mosque, and estimate the carbon emissions reduction resulting from installing solar panels. The study employed a quantitative research design and utilizes the Analytic Hierarchy Process (AHP) to select the most suitable solar panel type. The results reveal that polycrystalline solar panels are the optimal choice based on efficiency, power peak, operation and maintenance, and price criteria. Installing solar panels on the DIC Mosque's roof, positioned at an optimal height, ensures maximum sunlight exposure and energy generation efficiency. Calculations demonstrate a significant reduction in carbon emissions post-installation. The carbon emissions reduction potential is estimated at 57.693 kg CO2 eq per day or 21,057.95 tons CO2 eq per year. This highlights the positive environmental impact of solar energy implementation in the DIC Mosque.